Influence of Tetramethylammonium Hydroxide Cation Concentration on Omega Zeolite Crystal Size - Yahya, Muwafaq M.; AL-Rubaye, Rana T.; Al-Ani, Aqeel A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Omega zeolite nanocrystals can be synthesized hydrothermally from a sodium aluminosilicate solution characterized by a 5.96 Na2O/Al2O3 constant molar ratio, carried out at a maximum temperature of about 100°C for 4 days after aging at room temperature for 3 days, utilizing tetramethylammonium hydroxide (TMA-OH) at molar ratios of 0.36, 0.48, and 0.61. By using different analysis techniques, such as X-ray diffraction, energy dispersive X-ray spectroscopy, scanning electron microscopy, and atomic force microscopy, the physical characteristics of the nanosized omega zeolite crystals can be identified, and the omega zeolite crystal size can be regulated between 34 and 100 nm. In this research paper, the process of creating a uniform aluminosilicate solution with TMA-OH, followed by forming a solid aluminosilicate gel with adjusted elemental composition, reveals the significance of the TMA-OH/Al2O3 mole ratio for synthesizing nanocrystalline omega zeolite aggregates.